High-efficiency and wide-angle metasurface electromagnetic energy harvester - Cao, Anjie; Xu, Shuyin; Huang, Yeping; Zhang, Leiting; Liu, Cuijun; Chen, Zhansheng (Frontiers in Physics, 2024)
In today’s era of increasing energy constraints, harnessing the power of electromagnetic waves and converting them into directly usable energy has great potential in the field of renewable energy. This paper presents a highly efficient electromagnetic energy harvester with wide operation angles based on metasurface. The metasurface unit comprises four rotated copper rings plated on a Rogers RT5880 substrate. This unique design incorporates a 3.6 kΩ resistor within each of the four-cornered rotating metal rings, effectively emulating the input impedance circuit of a rectifier. Simulation results reveal that the metasurface achieves a remarkable electromagnetic wave harvesting efficiency of up to 92.3% at a frequency of 5.85 GHz. Additionally, it exhibits polarization insensitivity, enhancing its versatility and suitability for wide incident angles, which augments its practicality in various environments. The proposed metasurface energy harvester represents a significant advancement in electromagnetic energy collection technology, offering an efficient and reliable energy harvesting solution that contributes to addressing energy shortages and is applicable across multiple scenarios.